Diagnostic Bedside Vestibuloocular Reflex Evaluation in the Setting of a False Negative Fistula Test in Cholesteatoma of the Middle Ear - Ricardo D’Albora; Ligia Silveira; Sergio Carmona; Nicolas Perez-Fernandez (Case Reports in Otolaryngology)
Background. False negative fistula testing in patients with chronic suppurative otitis media is a dilemma when proceeding to surgery. It is imperative to rule out a dead labyrinth or a mass effect secondary to the cholesteatoma in an otherwise normally functioning inner ear. We present a case series of three patients in whom a bedside vestibuloocular reflex (VOR) evaluation using a head impulse test was used successfully for further evaluation prior to surgery. Results. In all three cases with a false negative fistula test we were able to further evaluate at the bedside and were not only able to register the abnormal VOR but also localize its deterioration to a particular semicircular canal eroded by the fistula. Conclusion. Vestibuloocular reflex evaluation is mandatory in patients with suspected labyrinthine fistula due to cholesteatoma of the middle ear before proceeding to surgery. We demonstrate successful use of a bedside head impulse test for further evaluation prior to surgery in patients with false negative fistula test.